The Effect of Continuous Wakefulness on Complex Cognitive Task Performance: A Quantitative Synthesis of Research. (September 2013) - Hutchins, S.D.; Laux, L.; Wickens, C.D.; Sebok, A.
In support of NASA's modeling and simulation goals to predict the effects of operator fatigue on performance, research findings from the literature on the effect of acute sleep deprivation on performance of complex cognitive tasks were quantitatively synthesized. Regression models of performance over continuous hours of wakefulness demonstrated complex cognitive task performance decrements for both speed and accuracy, with the greater performance decrement on speed over continuous hours of wakefulness. Circadian effects were also examined and reveal a greater decrement to both speed and accuracy performance over continuous hours of wakefulness during the circadian night than circadian day.